(untitled) (Global Journal of Management and Business Research, 2016)
This paper attempts to have an empirical analysis of the performance, growth, and potentiality of the Islamic Banking across the world with a particular reference to Bangladesh. To achieve its aim and objectives, initially, this paper reviewed the existing knowledge- followed by a qualitative method of documentation analysis of 8 Islamic banks in performance with 965 branches, 9 conventional banks with 20 branches of Islamic banking facilities and 7 conventional banks with 25 Islamic banking windows are providing Islamic banking services in Bangladesh. Comments are derived from the analysis of the findings of these banks. The findings revealed that Islamic Banking system becomes a popular term of banking to the people of Bangladesh.